Potential Alternatif Sources of Financing in Biofuel Development in Indonesia - Zahara, Amelia; Muslihin, Muslihin (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
Biofuels have been developed in many countries including Indonesia, which is an effort to reduce dependence on fossil energy sources. As one of the countries with a high population, has a large agricultural area and forest area, making Indonesia has the potential to become the highest biofuel producing country in the world. Since the government launched its energy policy in 2006 it seems interesting that, biofuel progress in Indonesia has not progressed well. The obstacles in the development of biofuels in Indonesia are government policies and infrastructure development funding systems. The target of the biofuel program in Indonesia seems very ambitious, therefore it needs alternative financing support outside the State Budget that can support the development of biofuels in Indonesia, which is the focus of this study. The research method is descriptive qualitative with a study that is, the potential for alternative sources of financing in the development of biofuels in Indonesia. The alternative financing taken is PINA (Government Non-Budget Investment Financing) which can contribute to financing the development of national strategic infrastructure projects with commercial value that has an impact on improving the economy in Indonesia.